ANALISIS KUALITAS AIR SUMUR GALI DI KAWASAN PARIWISATA SANUR - Trisnawulan, I.A.M.; Budiarsa Suyasa, I Wayan; Sundra, I Ketut (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2012)
parts of sampling areas: Sanur Kaja 5-6 meter (SA2) and 7-8 meter (SA3), Kelurahan Sanur 3-4 meter(SB1) and 5-6 meter (SB2), Sanur Kauh 3-4 meter (SC1) and 5-6 meter (SC2), using Cluster RandomSampling method.The result in April showed that from 14 parameters examined only 5 parameters have highconcentration than the acceptable drinking water standard (PPRI no.82, 2001). Those parameters areDissolved Oxygen (DO), Biochemical Oxygen Demand (BOD5), Nitrate (NO3), Phosphate (PO4), and TotalColi form. While the result of the analyses in June showed that 9 from 14 parameters have highconcentration than the acceptable drinking water standard ( PPRI no 82, 2001) they are Total DissolvedSolid (TDS), Dissolved Oxygen (DO), Biochemical Oxygen Demand (BOD5), Nitrate (NO3), Nitrite (NO2),Ammonia (NH3), Phosphate (PO4), E. coli and Total Coli form.The increasing concentrations indicate some pollution has occurred in these sampling areas. Theobservation has shown that most of the people in Sanur dump their waste water into the ground, which easilyabsorb through the porous soil then contaminate the ground water aquifer. Based on the water quality status using the pollution index, almost all the sampling areas have low pollution index, except the one at SanurKaja 7-8 m (SA3) has moderate pollution index.
Keywords: ground water, water quality, polluted water